Change of serum mitochondrial uncoupling protein 1 (UCP1) levels and daily rhythm of rectal and cutaneous temperatures in Equus caballus and Capra hyrcus. Issue 6 (2nd November 2017) - Giannetto, Claudia; Gianesella, Matteo; Arfuso, Francesca; Carcangiu, Vincenzo; Rizzo, Maria; Fazio, Francesco; Abbate, Francesco; Piccione, Giuseppe
Abstract: The aim of the present study was to monitor the daily rhythm of rectal and cutaneous temperatures together with the changes in the serum levels of mitochondrial uncoupling protein 1 (UCP1) in equine and goat species. On five gelding horses and five female goat rectal and cutaneous temperatures were recorded at 4 h intervals for a 48 h period. At the same time points blood samples were collected from each animal. Daily rhythms of rectal and cutaneous temperatures were observed in both species, in both day of monitoring. Mesor value of rectal temperature was statistically higher of about 4 °C than cutaneous temperature, and acrophase was postponed of about 2 h in both day of monitoring and in both species. UCP1 did not show daily rhythmicity in horses and goats. We can speculate that the thermogenesis due to thermal system is auxiliary to keeping the body temperature daily rhythm.